Influences of conservation measures on runoff and sediment yield in different intra-event-based flood regimes in the Chabagou watershed - Shan-Shan Wang (Nature Portfolio, 2021)
Abstract The Loess Plateau in China has suffered severe soil erosion. To control soil erosion, extensive conservation measures aimed at redistributing rainfall, hindering flow velocity and intercepting sediment were implemented on the Loess Plateau. To accurately evaluate the combined effect of conservation measures in the Chabagou watershed, this study classified intra-event-based floods into four regimes via cluster and discriminant analyses. Regime A was characterized by short flood duration and low erosive energy, regime B was characterized by short flood duration and high erosive energy, regime C was characterized by long flood duration and low erosive energy, and regime D was characterized by long flood duration and high erosive energy. The results indicated that peak discharge (q p ), runoff depth (H), mean discharge (q m ), and runoff erosion power (E) decreased by 75.2%, 56.0%, 68.0% and 89.2%, respectively, in response to conservation measures. Moreover, area-specific sediment yield (SSY), average suspended sediment concentration (SCE), and maximum suspended sediment concentration (MSCE) decreased by 69.2%, 33.3% and 11.9%, respectively, due to conservation measures. The nonlinear regression analysis revealed a power function relationship between SSY and E in both the baseline (1961–1969) and measurement period (1971–1990) in all regimes. Conservation measures reduced sediment yield by not only reducing the runoff amount and soil erosion energy but also transforming the flood regime, for example, transforming a high-sediment-yield regime into a low-sediment-yield regime. Moreover, conservation measures altered the SSY-E relationship in regime A, whereas no obvious difference in regime B or C/D was observed between the measurement period and the baseline period. This study provides a better understanding of the mechanism of runoff regulation and the sediment yield reduction under comprehensive conservation measures in a small watershed on the Chinese Loess Plateau.